Correlation between post-operative electrolyte changes to perioperative factors in Bipolar TURP - Anurag Dubey; Shivendra Singh Tiwari; Kumar, Santhosh; Paul Devaraj Vinent (Asian Journal of Medical Sciences, 2023)
Background: Transurethral resection of the prostate (TURP) is one of the best available treatments for benign hypertrophy of the prostate. Many of the complications in TURP are associated with the absorption of irrigation fluid. In BIPOLAR TURP, normal saline is used as an irrigant which is more physiological. Aims and Objectives: Our aim of the study is to evaluate the correlation between post-operative electrolyte changes to perioperative factors in bipolar TURP. Materials and Methods: One hundred and ten patients enrolled in this study who were admitted to Meenakshi Mission Hospital, Madurai, Tamil Nadu, India. Results: Mean age of the participants was 65.68 (±8.50) years with a median of 66 years. mean hemoglobin drop was 1.21 (±1.36) g/dl. The mean serum sodium drop was 1.55 (±3.01) mEq/L. The mean serum potassium change was 0.06 (±0.74) mEq/L. There was a significant positive association between operative time and serum sodium drop (P<0.001). There was no significant correlation between any of the other parameters prostate size, resection time, resected volume were noted, and post-operative electrolyte April 2019–March 2021. Patient pre-operative changes and hemoglobin drop is observed. Correlation is assessed with Spearman Rho. Conclusion: Our study concluded that as operative time increases sodium drop and hemoglobin drop significantly increases. Resected and pre-operative prostatic volumes do not affect electrolyte and hemoglobin levels.